2017
DOI: 10.1073/pnas.1705977114
|View full text |Cite
|
Sign up to set email alerts
|

SUPERMAN prevents class B gene expression and promotes stem cell termination in the fourth whorl of Arabidopsis thaliana flowers

Abstract: The molecular and genetic networks underlying the determination of floral organ identity are well studied, but much less is known about how the flower is partitioned into four developmentally distinct whorls. The SUPERMAN gene is required for proper specification of the boundary between stamens in whorl 3 and carpels in whorl 4, as superman mutants exhibit supernumerary stamens but usually lack carpels. However, it has remained unclear whether extra stamens in superman mutants originate from an organ identity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 36 publications
(39 reference statements)
6
70
0
1
Order By: Relevance
“…All Arabidopsis thaliana plants used were in the background of the Landsberg erecta (Ler) ecotype, except clf-28, yuc1 (SALK_106293), yuc4 (SALK_047083), and pDR5rev::GFP, which were from the Col-0 background and crossed into Ler at least three times. The sup-1, sup-5, clf-28, wus-1, yuc1, yuc4, pCUC2::3xVENUS-N7, pCLV3::GFP-ER, pSTM::CFP-N7, pSUP-SUP-3xVenusN7, pDR5rev::GFP, pDR5rev::3x-VENUS-N7, pRPS5A::DII-VENUS, and pDR5rev::2xGFP-N7 line were described previously (Bowman et al, 1989(Bowman et al, , 1992Sakai et al, 1995;Laux et al, 1996;Goodrich et al, 1997;Heisler et al, 2005;Cheng et al, 2006;Xu et al, 2006a;Gordon et al, 2007;Doyle & Amasino, 2009;Landrein et al, 2015;Liao et al, 2015;Prunet et al, 2017). Plants were grown at 22°C under 24 h of continuous light.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…All Arabidopsis thaliana plants used were in the background of the Landsberg erecta (Ler) ecotype, except clf-28, yuc1 (SALK_106293), yuc4 (SALK_047083), and pDR5rev::GFP, which were from the Col-0 background and crossed into Ler at least three times. The sup-1, sup-5, clf-28, wus-1, yuc1, yuc4, pCUC2::3xVENUS-N7, pCLV3::GFP-ER, pSTM::CFP-N7, pSUP-SUP-3xVenusN7, pDR5rev::GFP, pDR5rev::3x-VENUS-N7, pRPS5A::DII-VENUS, and pDR5rev::2xGFP-N7 line were described previously (Bowman et al, 1989(Bowman et al, , 1992Sakai et al, 1995;Laux et al, 1996;Goodrich et al, 1997;Heisler et al, 2005;Cheng et al, 2006;Xu et al, 2006a;Gordon et al, 2007;Doyle & Amasino, 2009;Landrein et al, 2015;Liao et al, 2015;Prunet et al, 2017). Plants were grown at 22°C under 24 h of continuous light.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…However, a recent example of a direct link between these two boundary types has come from study of the SUPERMAN (SUP) zinc finger gene. This is expressed in the crease separating stamen and carpel initiation zones where it may inhibit cell division (Sakai et al, 1995), as well as somehow preventing expression of the stamen identity gene AP3 from occurring in the adjoining carpel zone (Prunet et al, 2017).…”
Section: Reviewmentioning
confidence: 99%
“…For example, SIZF2 controls flower and leaf shape in A. thaliana. SUPERMAN (SUP) determines the boundary between the stamen and carpel whorls, suppresses class B gene expression and promotes stem cell termination in the fourth whorl of A. thaliana flowers [28][29][30]. In this study, 35 C2H2 genes showed no expression in the mutant capitula, which indicated that these C2H2 zinc finger protein genes may have important functions in the determination and growth regulation of pistils or anthocyanin synthesis and accumulation in the ray floret corolla in chrysanthemums.…”
Section: Many Transcription Factors Are Implicated In the Developmentmentioning
confidence: 70%